Genome-Wide Screen of the Hippocampus in Aged Rats Identifies Mitochondria, Metabolism and Aging Processes Implicated in Sevoflurane Anesthesia - Wang, Yujie; Qian, Min; Qu, Yinyin; Yang, Ning; Mu, Bing; Liu, Kaixi; Yang, Jing; Zhou, Yang; Ni, Cheng; Zhong, Jing; Guo, Xiangyang (Frontiers in Aging Neuroscience, 2020)
Previous studies have shown multiple mechanisms and pathophysiological changes after anesthesia, and genome-wide studies have been implemented in the studies of brain aging and neurodegenerative diseases. However, the genome-wide gene expression patterns and modulation networks after general anesthesia remains to be elucidated. Therefore, whole transcriptome microarray analysis was used to explore the gene expression patterns in the hippocampus of aged rats after sevoflurane anesthesia. 631 upregulated and 183 downregulated genes were screened out, then 44 enriched terms of biological process, 16 of molecular function and 18 of cellular component were identified by GO and KEGG analysis. Among them, oxidative stress, metabolism, aging and neurodegeneration were most enriched biological processes and changed functions. Thus, involved genes of these processes were selected for qPCR verification and a good consistency was confirmed. The potential signaling pathways were further constructed including mitochondrion and oxidative stress related Hifs-Prkcd-Akt-Nfe2l2-Sod1 signaling, multiple metabolism signaling (Scd2, Scap-Hmgcs2, Aldh18a1-Glul and Igf1r), as well as aging and neurodegeneration related signaling (Spidr-Ercc4-Cdkn1a-Pmaip1 and Map1lc3b). These results provide potential therapeutic gene targets for brain function modulation process after inhaled anesthesia in the elderly, which could be valuable for preventing postoperative brain disorders and diseases, such as perioperative neurocognitive disorders, from genetic level in the future.